Modelling knowledge transfer of nursing students during clinical placement / Nor Azairiah Fatimah Othman - Othman, Nor Azairiah Fatimah (2016)
The current study explored factors affecting behavioral of knowledge transfer and the antecedents predicting this within the Theory of Planned Behavior (TPB) framework. This study made an attempt to incorporate knowledge transfer-related variables (articulability of knowledge, credibility of knowledge source, gap of theory-practice, embedded knowledge and environmental uncertainty) into the framework. The premise of the model is to provide guideline of necessary conditions that are influential to knowledge transfer behavior in the clinical placement. It is hoped that by holistically understanding and paying closer attention to these predictors, a more comprehensive strategy can be devise beforehand to alleviate any problems that might negatively hinder activities of acquiring and applying new knowledge at the point of clinical placement, which subsequently maximize required clinical experience and in turn increase the levels of clinical competence. The posited model was validated quantitatively using field surveys to one of key stakeholders of clinical placement; the nursing students. The influence of the variables selected for this study was tested on two distinct samples of Lower Semester Group, LSG (semester 1- 3) and Higher Semester Group, HSG (semester 4-6) separately. A total of 2880 questionnaires were distributed to nursing students from all government-affiliated nursing institutions throughout the country. A total of 2779 (96.5%) was returned and only 2638 were usable for analysis. Data analysis statistical technique of Partial Least Square (PLS) was conducted to analyze the hypothesized relationships and to test adequacy of the proposed model. For LSG, eight (8) of ten (10) hypotheses were supported. For HSG, with excerption to three (3), all of the hypothesized paths are in the direction hypothesized. The Model show reasonably good fit supported by the acceptable level of the GoF indices of 0.389 (LSG) and 0.383 (HSG). The finding of this study which is solely focuses on knowledge transfer from the recipient of the knowledge perspective, is contributing to the existing TPB framework and knowledge transfer literature with new measures, constructs and structural paths added in rarely tested context; clinical placement. The study could provide direction for nursing authority in directing appropriate resources that are conducive to knowledge transfer at clinical placement when developing nursing curriculum structures in the future.